Microscopic Stages of North Atlantic Laminaria digitata (Phaeophyceae) Exhibit Trait-Dependent Thermal Adaptation Along Latitudes - Schimpf, Nele M.; Liesner, Daniel; Franke, Kiara; Roleda, Michael Y.; Bartsch, Inka (Frontiers in Marine Science, 2022)
Kelp forests in the North Atlantic are at risk of decline at their warm temperature distribution margins due to anthropogenic temperature rise and more frequent marine heat waves. To investigate the thermal adaptation of the cold-temperate kelp Laminaria digitata, we sampled six populations, from the Arctic to Brittany (Spitsbergen, Tromsø, Bodø [all Norway], Helgoland [Germany], Roscoff and Quiberon [both France]), across the species’ entire distribution range, spanning 31.5° latitude and 12-13°C difference in mean summer sea surface temperature. We used pooled vegetative gametophytes derived from several sporophytes to approximate the genetic diversity of each location. Gametophytes were exposed to (sub-) lethal high (20-25°C) and (sub-) optimal low (0-15°C) temperature gradients in two full-factorial, common-garden experiments, subjecting subsets of populations from different origins to the same conditions. We assessed survival of gametophytes, their ability to develop microscopic sporophytes, and subsequent growth. We hypothesized that the thermal performance of gametophytes and microscopic sporophytes corresponds to their local long-term thermal history. Integrated gametophyte survival revealed a uniform upper survival temperature (UST) of 24°C among five tested populations (Tromsø to Quiberon). In contrast, following two weeks of thermal priming of gametophytes at 20-22°C, sporophyte formation at 15°C was significantly higher in southern populations (Quiberon and Roscoff) compared to the high-latitude population of Tromsø. Between 0-15°C, survival of the Arctic population (Spitsbergen) was negatively correlated with increasing temperatures, while the southern-most population (Quiberon) showed the opposite. Thus, responses of survival at low, and sporophyte formation at high temperatures, support the concept of local adaption. On the other hand, sporophyte formation between 0-15°C peaked at 6-9°C in the Quiberon and at 9-12°C in the Spitsbergen population. Sporophyte growth rates (GR) both in length and width were similar for Spitsbergen, Tromsø and Quiberon; all had maximum GRs at 12-15°C and low GRs at 0-6°C. Therefore, responses of sporophyte formation and growth at low temperatures do not reflect ecotypic adaptation. We conclude that L. digitata populations display trait-dependent adaptation, partly corresponding to their local temperature histories and partly manifesting uniform or unpredictable responses. This suggests differential selection pressures on the ontogenetic development of kelps such as L. digitata.